2014
DOI: 10.1016/j.ijheatmasstransfer.2014.07.054
|View full text |Cite
|
Sign up to set email alerts
|

Melting and solidification enhancement using a combined heat pipe, foil approach

Abstract: Melting and solidification of a phase change material is investigated, experimentally and computationally, using a novel heat pipe-metal foil approach. By embedding a PCM within a metal foil matrix, and delivering (or extracting) thermal energy to (or from) the matrix with a vertically-oriented heat pipe, overall thermal resistances between a working fluid and the PCM solid-liquid interface can be reduced. This leads to increased phase change rates relative to configurations involving only the heat pipe, or on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(33 citation statements)
references
References 30 publications
0
33
0
Order By: Relevance
“…The results indicated that employing HPs makes considerable improvement in both melting and solidification rates. Sharifi et al [35] investigated the melting and solidification of n-Octadecane (T m = 28°C) using heat http://dx.doi.org/10.1016/j.enconman.2014. 10.053 0196-8904/Ó 2014 Elsevier Ltd. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that employing HPs makes considerable improvement in both melting and solidification rates. Sharifi et al [35] investigated the melting and solidification of n-Octadecane (T m = 28°C) using heat http://dx.doi.org/10.1016/j.enconman.2014. 10.053 0196-8904/Ó 2014 Elsevier Ltd. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…A HP-foil configuration and similarly configured HP-foam system (with aluminum foam replacing the aluminum foil, foam porosities greater than 0.870, and pore densities ranging from 5-40 pores per inch) was also investigated by Allen et al [62,63]. Similar to the results of [61], in [62], the foil-enhanced system (with a porosity of 0.957) exhibited PCM melting (solidification) rates that were nearly 15 (8) times that of the bare rod configuration. The HP-foil system also outperformed the HP-foam system despite the lower porosity (higher metal volume fraction) of the HP-foam system.…”
Section: General Thermal Energy Storage Applicationsmentioning
confidence: 86%
“…A PCM-HPHX was investigated by Sharifi et al [61] in which a cylinder housed a PCM and a concentrically-located HP. The PCM was further enhanced with aluminum foils (resulting in a PCM-foil matrix porosity of 0.987).…”
Section: General Thermal Energy Storage Applicationsmentioning
confidence: 99%
“…The integral solution was validated by comparison with computational results obtained from a control volume code based on the temperature transforming method [1]. Validation studies of the code against experimental results has been reported in prior publications by one of the authors [23,24]. Due to the conduction-controlled phase change, the momentum and pressure correction equations where deactivated in the computational model and only the energy equation was solved:…”
Section: Validationmentioning
confidence: 99%